Enhancing Dissolution and Bioavaibility of Purely Water Insoluble Natural Compounds by Solid Dispersion with Hot Melt Extrusion Technique - Sofi Nurmay Stiani; Taofik Rusdiana; Anas Subarnas (Journal of Global Pharma Technology, 2018)
The use of herbal remedies is still a trend in the world, especially Indonesia as the second largest country after Brazil is rich in medicinal plants, in addition to having many pharmacological properties also have low side effects. The most common problems with biopharmaceutically related natural substances are low drug solubility, low biopharmaceutics, stability problems and active substance absorption. Bioavailability is an important factor in achieving the effects of drug therapy. Low bioavailability may occur due to low water solubility, instability in the digestion, and difficulty passing through the membrane. To overcome the problem of bioavaibility of natural material compounds should be made efforts to improve it, one of them with solid dispersion method. The solid dispersion is the dispersion of one or more active ingredients in an inert solid carrier. Technique of Dispersion in the carrier can be by way of hot spin mixing, co-evaporation, co-precipttion, freeze-drying, spray drying and HME. Techniques that are still rarely used in Indonesia is hot melt extrusion (HME). This study aims to explore characteristics of the chemical properties of natural materials, efforts to increase the bioavailability of natural compounds, and solid dispersion techniques.Keywords: Bioavailability, Natural compounds, solid dispersion, hot melt extrusion